Financial Distress and the Commitment to Promoting Innovation in State-Owned Enterprises: A Critical Perspective - Ansyah, Rahmat Husein Andri; Firmansyah, Akbar Maulana (Badan Pemeriksa Keuangan Republik Indonesia, 2023)
Financial distress in State-Owned Enterprises (SOEs) has been a problematic issue for a long time. By 2020, the total debt of SOEs in Indonesia reach 1.682 trillion Rupiahs, whereas 68% out of all SOEs that receive state capital injections are facing bankruptcy. However, a more critical perspective still needs to investigate how commitment to promoting innovation relates to financial distress in SOEs. The existing studies of financial distress in SOEs have mainly focused on analyzing technical and structural factors and the predictive models using company financial indicators. This study aims to analyze the financial distress and innovation in SOEs critically. This study uses official data of PT Krakatau Steel from 2015-2020 and employs the combined analysis method. Quantitative regression analysis analyzes the company's financial distress throughout the period. In contrast, qualitative content analysis analyzes the relevance of the company's innovation commitment in the same period. The study shows that apart from ineffective capital structure decisions, low commitment to innovation is an important factor influencing financial distress in SOEs. The prospect of restructuring as a short-term strategy is also discussed.